2006
DOI: 10.1007/s11205-005-3247-2
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Child Health in Pakistan: An Economic Analysis

Abstract: child health, latent variables, MIMIC models, stock of health, unobservability, 112,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…However, in Middle Eastern countries and African countries, it has been observed that child mortality rate has been declined along with a reduction in economic growth. It implies that income is not the single variable that affects the child mortality; there are some other factors that affect the child mortality (Cutler, Deaton, & Lleras-Muney, 2006;Shehzad, 2006).…”
Section: Health Expenditure and Child Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, in Middle Eastern countries and African countries, it has been observed that child mortality rate has been declined along with a reduction in economic growth. It implies that income is not the single variable that affects the child mortality; there are some other factors that affect the child mortality (Cutler, Deaton, & Lleras-Muney, 2006;Shehzad, 2006).…”
Section: Health Expenditure and Child Mortalitymentioning
confidence: 99%
“…A few studies observed that child mortality rate decreases when economic growth increase (Van den Berg, Lindeboom, & Portrait, 2006) but some studies found that economic growth is not a powerful determinant of child mortality because it has low and in some cases no association with child mortality (Filmer, 1999;Maruthappu et al, 2017). Especially in low-income countries where political and local administration is corrupt and give low priority to social indicators (Shehzad, 2006).…”
Section: Health Expenditure and Child Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review confirmed that wages, medical prices, education, and age were consensus variables in estimating health demand. Some researchers have found wages have a positive effect on health demand -this positive effect is that wages increase the health stock [13], [14], [19], [20], [21], [22], [23]. In contrast to Gupta and Grave [24] who found the effect was not significant.…”
Section: Methodsmentioning
confidence: 99%
“…Pov-erty and low socioeconomic status are associated with higher risk of death in infancy and childhood, chronic childhood illness, and many acute illnesses. It has also been found that the longer the child is exposed to adverse social conditions and he worse the social conditions, the greater the effect (Smith, 1999;Wagstaff et al, 2004;Armar -Klemesu, 2004;Shehzad, 2006).…”
Section: Use Of Bed-netsmentioning
confidence: 99%